Gestión y desarrollo agroturístico de la parroquia Cumandá, cantón Palora - Sotomayor Gualpa, Inés Mercedes (2022)
ABSTRACT Tourism management within the Cumandá parish has been carried out in an inadequate way, due to several factors, with little knowledge being one of the main problems, which is why there are several projects focused on having a better development of Agrotourism , the main economic activity that generates benefits for the locality. The main objective of the research is to analyze the existing influence between the management with the agrotourism development of the Cumandá Parish, Palora Canton. For this, the methodology used is descriptive, exploratory and correlational-causal, since all the information collected was based on primary and secondary bibliographic sources. The design is non-experimental and transactional or causal cross-sectional, since evaluation instruments were applied at a single time and date. The technique used was the survey which was designed under a questionnaire on a Likert scale. Quantitative data was collected through the application of surveys to 5 professionals in charge of the management and tourist direction of the parish and 80 tourists who visit it. Based on the results, it was possible to observe that the planning, direction and organization regarding the tourist management of Cumandá has been carried out in an adequate manner. However, there are particularities in agrotourism projects that must be reconsidered in order to obtain local development. Once the investigative work has been analyzed, the design of a tourist product is proposed. focused on meeting the expectations and needs of tourists, as well as making local and foreign tourists aware of the agro-tourism activities of the parish. The tourism product is made up of three tour packages that combine natural attractions, cultural events, extreme sports and activities agrotourism, components that arouse the interest of visitors. Keywords: Management, development, agrotourism, planning, direction.